(untitled) (Altre Modernità, 2025)
In Mercurio e Marte (1628), the inaugural performance at the Farnese Theatre in Parma with dramaturgy by Claudio Achillini and music by Claudio Monteverdi, we find some of the practices characteristic of Renaissance and Baroque entertainment: the artisanal, collective and multidisciplinary organization of the performance, the presence of specialized technicians and the practice of reuse. As the climax of the celebrations for the wedding of Odoardo Farnese and Margherita de’ Medici, this opera-tournament is the ideal setting to represent the ambitions of the patrons through symbol, allegory and stage machinery. The production was based on the text, scenes and machinery prepared ten years earlier for La difesa della bellezza, a performance originally conceived to inaugurate the theatre in anticipation of a hoped-for but never realized visit by Cosimo II de’ Medici, with whom the Duke of Parma Ranuccio I wanted to form an alliance. This article analyzes the extent of the reuse of scenes and machinery by comparing the archival documents for La difesa della bellezza and Mercurio e Marte. The aim is to confirm the prevalence of a practice which, in antiquity, had the purpose of reusing the resources provided by the court so as not to undo previous productive and economic endeavors.